2020
DOI: 10.1088/1755-1315/548/3/032001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of shape and asymmetry in rye leaf

Abstract: The variability of bilateral structures is associated with the stability of development; the populations attribute which characterizes homeostasis of plant development at the epigenetic level. A violation in the functioning of regulatory proteins creates a deviation from the norm in fluctuating asymmetry, as a measure of ontogenetic noise. To test the variability of the shape and asymmetry of winter rye leaf plates depending on the dose of mineral fertilizer, we used the Generalized Procrustes analysis and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…As previous studies have shown, the photographing error is extremely small, therefore, the image was acquired once, and the labeling with subsequent processing was carried out twice. The procedure for applying true landmarks of the first type was carried out with the splitting of the entire contour into equal segments, and is described in detail in previous works [20][21].…”
Section: Methods Of Geometric Morphometricsmentioning
confidence: 99%
“…As previous studies have shown, the photographing error is extremely small, therefore, the image was acquired once, and the labeling with subsequent processing was carried out twice. The procedure for applying true landmarks of the first type was carried out with the splitting of the entire contour into equal segments, and is described in detail in previous works [20][21].…”
Section: Methods Of Geometric Morphometricsmentioning
confidence: 99%